2011
DOI: 10.1186/1752-1947-5-42
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphic features of Morquio's syndrome: a case report

Abstract: IntroductionTo the best of our knowledge, we present for the first time the bone scintigraphy findings of a patient with Morquio's syndrome.Case presentationA 46-year-old Caucasian man with Morquio's syndrome presented with lower back pain six weeks after a left total hip replacement. A whole body bone scan demonstrated an anthropomorphic skeletal pattern consistent with a mucopolysaccharide storage disease, thereby showing the cause of the patient's pain.ConclusionsTo the best of our knowledge, the bone scint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Excessive urinary levels of keratin sulfate are confirmatory. Except for a recent study of Kitzing and Allman, who reported scintigraphic features in a case a Morquio's syndrome, no other studies have been recently published presenting a systematic imaging collection of this rare disease [ 8 ]. The aim of our study is therefore to describe the unique radiographic and MRI associated skeletal deformities in an adult case of type IV B Morquio syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive urinary levels of keratin sulfate are confirmatory. Except for a recent study of Kitzing and Allman, who reported scintigraphic features in a case a Morquio's syndrome, no other studies have been recently published presenting a systematic imaging collection of this rare disease [ 8 ]. The aim of our study is therefore to describe the unique radiographic and MRI associated skeletal deformities in an adult case of type IV B Morquio syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Morquio syndrome is a rare genetic disease of unknown frequency, it is assumed to be inherited autosomal recessive disease. Metabolic disorder of mucopolysacharides, alteration of bones and internal organs, as well as distinctive appearance of the patient is characteristic for this syndrome [26].…”
Section: Syndromes and Diseases Associated With Structural Abnormalitmentioning
confidence: 99%
“…Sma tra se da se na sle đu je auto zom no re ce sivno. Od li ku ju je: po re me ćaj me ta bo li zma mu ko po li sa ha ro i do za, pro me ne na ko sti ma i unu tra šnjim or ga ni ma i ka rak te ri sti čan iz gled bo le sni ka [26].…”
Section: Sindromi I Bolesti Koji Su U Vezi Sa Strukturnim Anomalijamaunclassified